Cognitive load of critical thinking strategies. (February 2015) - Shehab, Hanem M.; Nussbaum, E. Michael
Abstract: Argument–counterargument integration (Nussbaum, 2008 ) refers to the process of evaluating, refuting, and synthesizing arguments on two sides of an issue when creating justification for an overall conclusion. This study compared the cognitive load of two critical thinking strategies related to argument–counterargument integration: (a) constructing design claims that minimize disadvantages of an alternative, and (b) weighing refutations (which weaken an argument by arguing that there are more important values at stake). College students ( N = 285) first completed the Need for Cognition (NFC) scale and were then presented with materials summarizing arguments and counterarguments on the topic of grading class participation. Participants completed a small, integrative essay justifying a stand on the issue, and completed the Mental Effort Rating Scale (Paas, 1992 ). Participants who generated complex weighing refutations reported more mental effort than those constructing complex design claims (and the control group), with a stronger relationship with those high in NFC. The need to coordinate disparate elements in working memory may explain the higher load associated with constructing weighing refutations. Students may need more (and different types of) scaffolding in using this strategy than when constructing a design claim, which is a more sequential process. Highlights: Integrating arguments/counterarguments through weighing both sides involves more mental effort than designing a solution. This effect was more prominent for students with high need for cognition. Students who constructed a solution required more time, compared to students in the control group.